THE FACTORS INFLUENCING TECHNOLOGY ADOPTION PROCESS OF FARMERS IN TERM OF AGRICULTURAL EXTENSION POLICY CASE IN CENTRAL JAVA INDONESIA - Muhamad Rusliyadi; Yanuar Wahyu Yudistira Ardi; Kodrad Winarno (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Agricultural extension activities as a form of educational facilities for the community, especially farmers have an important role in making changes with innovations delivered to farmers and making faster adoption to the field. The adoption problem process of innovation can affect the occurrence of behavior changes that can be observed directly or indirectly and give some different gap adoption to the farmer. The study aims to define the application of binary logistics regression in analyzing the factors which that influence the adoption process of innovative technology in vegetable farmers. The research method was used descriptive analysis and binary logistic regression analysis are utilized to analyze the data used in the assessment's implementation. The results of the research after some analysis of stages such as the formation of the initial model test, simultaneous tests, partial test, and model match test obtained.  The results of the factors that affect the adoption process of technology is a factor in the number of livestock and vegetable with a value of 0.006 (p < 0.05)  was a significance, an intensity factor of extension with the value of 0.039 (p < 0.05) was a significance, a factor in the distance of residential of women farmers groups to the source of innovation with value of 0.020 (p < 0.05) was a significance, and the distance factor of the residential of farmers to the source of capital with a value of 0.010 (p < 0.05) was a significance. The research showed that the probability factor influencing of the process technology adoption base on the distance farmer from the capital and sources innovation, the intensity of extensions and also number of livestock and vegetable.